The mitochondrial genome of Leuctra sp. (Plecoptera: Leuctridae) and its performance in phylogenetic analyses - Shen, Yue; Du, Yu-Zhou (Zootaxa, 2019)
The nearly complete mitochondrial genome (mitogenome) of Leuctra sp. (Plecoptera: Leuctridae) was sequenced. The 14,585-bp long mitogenome of L. sp. contained 37 genes including 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and a control region (CR). The mitochondrial gene arrangement of L. sp. was identical with other stoneflies and the putative ancestral mitogenome of Drosophila yakuba Burla. Most PCGs used standard ATN start codons and TAN termination codons. Twenty-one of the 22 tRNAs in each mitogenome exhibited the cloverleaf secondary structures, while the dihydrouridine (DHU) arm of trnSer (AGN) was reduced. Phylogenetic analyses using our new Leuctra sp. genome and all other publicly available genomes for Plecoptera and Bayesian inference (BI) and maximum likelihood methods (ML) generated identical topologies, both supporting the monophyly of all stonefly families for which tests were possible and the infraorder Systellognatha. Scopuridae and Gripopterygidae were grouped with the infraorder Euholognatha. The final relationships within Plecoptera were recovered as (((((Perlodidae + Chloroperlidae) + Perlidae) + Pteronarcyidae) + Peltoperlidae) + Styloperlidae) + (((((Capniidae + Taeniopterygidae) + Nemouridae) + Scopuridae) + Leuctridae) + Gripopterygidae).